Continuous Surface Rendering, Passing from CAD to Physical Representation. (19th June 2013) - Covarrubias, Mario; Bordegoni, Monica; Cugini, Umberto
This paper describes a desktop-mechatronic interface that has been conceived to support designers in the evaluation of aesthetic virtual shapes. This device allows a continuous and smooth free hand contact interaction on a real and developable plastic tape actuated by a servo-controlled mechanism. The objective in designing this device is to reproduce a virtual surface with a consistent physical rendering well adapted to designers' needs. The desktop-mechatronic interface consists in a servo-actuated plastic strip that has been devised and implemented using seven interpolation points. In fact, by using the MEC (Minimal Energy Curve) Spline approach, a developable real surface is rendered taking into account the CAD geometry of the virtual shapes. In this paper, we describe the working principles of the interface by using both absolute and relative approaches to control the position on each single control point on the MEC spline. Then, we describe the methodology that has been implemented, passing from the CAD geometry, linked to VisualNastran in order to maintain the parametric properties of the virtual shape. Then, we present the co-simulation between VisualNastran and MATLAB/Simulink used for achieving this goal and controlling the system and finally, we present the results of the subsequent testing session specifically carried out to evaluate the accuracy and the effectiveness of the mechatronic device.